The Impact of Online Worship on Church Growth During the Covid-19 Pandemic at GBI Kasih Karunia Bogor - Djone Georges Nicolas; Adolf Bastian Butar-butar; Timothy Amien Rk; Soneta Sang Surya Siahaan; Simon Marbun (Indonesian Journal of Advanced Research, 2023)
The purpose of this study was to find out how big the impact of online worship was on the quantity of church growth at Bethel Indonesia Kasih Karunia Bogor Church during the Covid-19 pandemic, using a quantitative method approach, and collecting data from the Bible and various books and journals, and submitting questionnaires to 30 people, including pastors and church officials, as well as congregations that have been involved in ministry for more than 2 years, through correlation and regression analysis by measuring variables and analyzing data through statistics. As a result, there is an effect of online worship on church growth in quantity at the Bethel Indonesia Kasih Karunia Bogor Church, which is indicated by a correlation coefficient value of 0.847 which has a significant effect of 71.8 percent and is very significant at = 0.05 (5%).